Cost-Benefit Analysis of Solar Energy Integration in Buildings: A Case Study of Affordable Housing in Brazil - Vasco-Calle, D (Frontiers Media SA, 2023)
Introduction: The construction sector plays a pivotal role in global natural resource consumption, underscoring the urgency of promoting energy efficiency in buildings. With the escalating demand for renewable energy, solar power has gained significant traction. This study focuses on conducting a comprehensive cost-benefit analysis of solar energy integration in residential buildings. Methods: The approach involves a novel comparison between photovoltaic panels and Solar Heating Systems (SHS) based on both environmental and financial considerations. To evaluate the practical implications, a case study was undertaken on an affordable housing complex in Brazil. Three distinct models were simulated for analysis: Model 1, featuring a grid-connected photovoltaic project with zero energy balance; Model 2, incorporating a grid-connected photovoltaic project with two solar panels generating 340 W each; and Model 3, integrating an SHS. Results: The findings reveal the technical and economic feasibility of all proposed models. Model 1 stands out with superior performance in terms of estimated energy generation, energy savings, and annual reduction of CO2 emissions. On the other hand, Model 3 excels in the financial analysis, indicating its viability from a cost perspective. Discussion: This research contributes to informed decision-making processes regarding the utilization of photovoltaic panels and SHS, thereby fostering energy efficiency and sustainability in buildings. The nuanced comparison of environmental and financial aspects provides valuable insights for stakeholders in the construction and renewable energy sectors. The identified strengths and trade-offs of each model enable a more holistic understanding of the implications of solar energy integration in residential buildings. Copyright © 2023 De Arruda, Figueiredo, Vasco, Haddad and Najjar.